2011
DOI: 10.1179/2042618610y.0000000003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neurodynamic mobilization on fluid dispersion within the tibial nerve at the ankle: an unembalmed cadaveric study

Abstract: Objective: To evaluate the effects of neurodynamic mobilization on the fluid dynamics of the tibial nerve in cadavers. Background: Evidence showing patients benefit from neural mobilization is limited. Mechanisms responsible for changes in patient symptoms are unclear. Methods: Bilateral lower limbs of six unembalmed cadavers (n512) were randomized into matched pairs and dissected to expose the tibial nerve proximal to the ankle. Dye composed of Toulidine blue and plasma was injected into the nerve. The longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 72 publications
2
44
0
4
Order By: Relevance
“…However, the underlying mechanisms associated with clinical improvements following neural mobilization remain unclear. 11 There are many theories that have been postulated, including physiological effects (removal of intraneural edema 11,15,20,28,44 ), central effects (reduction of dorsal horn and supraspinal sensitization 13,15,21 ), and mechanical effects (enhanced nerve excursion 15,18,21,22,28,38,44 ). Future research needs to focus on uncovering the underlying mechanisms of neural mobilization.…”
Section: T T Conclusionmentioning
confidence: 99%
“…However, the underlying mechanisms associated with clinical improvements following neural mobilization remain unclear. 11 There are many theories that have been postulated, including physiological effects (removal of intraneural edema 11,15,20,28,44 ), central effects (reduction of dorsal horn and supraspinal sensitization 13,15,21 ), and mechanical effects (enhanced nerve excursion 15,18,21,22,28,38,44 ). Future research needs to focus on uncovering the underlying mechanisms of neural mobilization.…”
Section: T T Conclusionmentioning
confidence: 99%
“…13 The rationale for using neurodynamic in diagnosis and treatment is that they are considered capable of detecting the increased nerve mechanosensitivity associated with these conditions. 14,15 …”
Section: Resultsmentioning
confidence: 99%
“…11 Neuro dynamic, i.e., the mobilization of the peripheral nervous system, is a physical approach to the treatment of pain; the method relies on influencing pain physiology via mechanical treatment of neural tissues and the non-neural structures surrounding the nervous system. 2,13 Through clinical reasoning the nervous system seems to be the logical place for treatment and explanations, although previous descriptions of this method have not clarified the relevant mechanics and physiology, including interactions between these two components. Within this reasoning it is important to determine and develop clinical research to ascertain the diagnostic value of neurodynamic sequencing in damaged neural tissue.…”
mentioning
confidence: 99%
“…Neurodynamic testing had been validated for its use in detecting peripheral neuropathic pain [124], and it was Boyd et al [125] demonstrated diminished mechanosensitivity of lower extremity peripheral nerves in individuals with peripheral neuropathy. Neurodynamic mobilization was shown to improve intraneurial fluid dispersion of tibial nerve in a cadaveric study and was suggested to be indicated for peripheral neuropathic pain syndromes [126].…”
Section: Manual Therapymentioning
confidence: 99%